Hubungan Fase Pengobatan dengan Kualitas Hidup Pasien TB di Puskesmas Perumnas I Pontianak, Indonesia: Penelitian - Nabila, Jihan; Fitriangga, Agus; Putri, Eka Ardiani (Cermin Dunia Kedokteran, 2026)
Introduction: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis, also known as acid-fast bacteria. One measure to control TB cases is treatment. The success of treatment affects the quality of life of patients with TB. Medication can improve the quality of life among tuberculosis (TB) patients. This study aims to determine the relationship between the treatment phase and the quality of life among TB patients at Puskesmas Perumnas I, Pontianak. Methods: Cross-sectional observational analytic study and a total sampling method with 23 TB patients as subjects. The quality of life was assessed with WHOQOL-BREF. Univariate and bivariate data analysis was carried out using the Fisher correlation coefficient. Univariate analysis was used to examine the distribution of research subject characteristics, while bivariate analysis was used to determine the relationshipbetween treatment phase and quality of life. Results: There is a significant relationship between the treatment phase and the quality of life of tuberculosis patients at the Perumnas I Pontianak Health Center (Sig. (2-tailed) p = 0.005). Conclusion: There is a significant relationship between the treatment phase and the quality of life of tuberculosis patients at the Perumnas I Pontianak Health Center.